2020
DOI: 10.1155/2020/8985424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hybridization in Two African Catfishes (Siluriformes, Clariidae): Exotic (Clarias gariepinus Burchell, 1822) and Native (Clarias jaensis Boulenger, 1909) Species under Controlled Hatchery Conditions in Cameroon

Abstract: The study was conducted to evaluate reciprocal hybridizations in the African catfishes Clarias gariepinus and Clarias jaensis using artificial reproduction under controlled hatchery conditions. The results revealed that the highest fertilization (82.77%) and hatching (67.77%) rates were achieved in the hybrid cross female C. jaensis × male C. gariepinus (Fcj × Mcg). Deformed larvae rates ranged from 9.01 to 16.33%; the hybrid Fcj × Mcg recorded the lowest rate. Survival rates in the larval stage were higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…To get the highest hatchability rate, hybrid crossing is thus encouraged. This is also in agreement with the report of [23], who reported that the highest fertilization (82.77%) and hatching (67.77%) rates were achieved in the hybrid cross between female Clarias jaensis × male Clarias gariepinus. [24] also reported that hybridization enhances reproduction indices when they assessed the effect of hybridization on the fecundity of Oreochromis karongae.…”
Section: Discussionsupporting
confidence: 93%
“…To get the highest hatchability rate, hybrid crossing is thus encouraged. This is also in agreement with the report of [23], who reported that the highest fertilization (82.77%) and hatching (67.77%) rates were achieved in the hybrid cross between female Clarias jaensis × male Clarias gariepinus. [24] also reported that hybridization enhances reproduction indices when they assessed the effect of hybridization on the fecundity of Oreochromis karongae.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, the African catfish is considered an excellent biological model for studying amphibious traits (i.e., bimodal breathing) and terrestrial transition [16][17][18] . However, current genomics research has primarily focused on phylogenetic and domestication studies 9,[19][20][21] , as well as on sex-chromosome and karyotype evolution utilizing only a limited panel of molecular markers [22][23][24] .Clarias gariepinus genome is made up of 2n = 2x = 56 chromosomes (18 m + 20 sm + 18 st/a) 25 with a fundamental number (NF) of 94. Its chromosome system has historically been contentious.…”
mentioning
confidence: 99%
“…As a result, the African catfish is considered an excellent biological model for studying amphibious traits (i.e., bimodal breathing) and terrestrial transition [16][17][18] . However, current genomics research has primarily focused on phylogenetic and domestication studies 9,[19][20][21] , as well as on sex-chromosome and karyotype evolution utilizing only a limited panel of molecular markers [22][23][24] .…”
mentioning
confidence: 99%